2019
DOI: 10.20429/ijsotl.2019.130310
|View full text |Cite
|
Sign up to set email alerts
|

Integrating The Five Practices of Exemplary Leadership Model into Entrepreneurship Education

Abstract: Entrepreneurship educators can assess their students by focusing on leadership self-efficacy dimensions that align with desirable entrepreneurship behaviors. To support this claim, we used the Student Leadership Practices Inventory (S-LPI) to survey a group of 46 undergraduate students in Mexico and 49 undergraduate students in Spain that were involved in entrepreneurship education programs. Independent samples t-tests show statistically significant differences between the two groups. We also compared the whol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
0
4
1
Order By: Relevance
“…The results presented here would seem to challenge the findings in previous research involving leadership and gender conducted by Díaz (2018) and Díaz et al (2019). In those studies, no significant differences were identified between females and males across leadership factors.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…The results presented here would seem to challenge the findings in previous research involving leadership and gender conducted by Díaz (2018) and Díaz et al (2019). In those studies, no significant differences were identified between females and males across leadership factors.…”
Section: Discussioncontrasting
confidence: 94%
“…In one study conducted under Kouzes and Posner's model with undergraduate Mexican and Spanish students, nation of origin resulted in significant differences in the shared vision dimension, but no differences were reported when the group was divided by gender (Díaz, Sánchez-Vélez, & Santana-Serrano, 2019). The fact that females and males attributed similar levels of importance to this factor suggest that gender does not moderate consensus building and establishing shared goals and supports the claim that gender does not moderate TL.…”
Section: Discussionmentioning
confidence: 91%
“…A teacher is expected to be an example so that students can reflect on their personality. The word exemplary comes from the basic word "exemplary" (Diaz et al, 2019). The word "exemplary" is something that should be imitated or imitated (Sandi et al, 2022).…”
Section: Be An Examplementioning
confidence: 99%
“…Leaders practice five key positive behaviors when they lead their people (Díaz et al, 2019). When leaders incorporate positive leadership practices, their people will have a clear direction, more self-awareness, feel emboldened, and show cooperation (Hagan et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%